2015
DOI: 10.1136/bjophthalmol-2014-305893
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis and successful treatment of paraneoplastic melanocytic proliferation

Abstract: BackgroundParaneoplastic melanocytic proliferation (bilateral diffuse uveal melanocytic proliferation, BDUMP) is a rare but devastating disease that causes progressive visual loss in patients who usually have an occult malignancy. Visual loss occurs as a result of paraneoplastic changes in the uveal tissue.MethodsIn a masked fashion, the serum of two patients with BDUMP was evaluated for the presence of cultured melanocyte elongation and proliferation (CMEP) factor using cultured human melanocytes. We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 12 publications
4
33
0
Order By: Relevance
“…This observation was further supported by Jansen et al. () , who reported two cases of BDUMP in whom serum were collected. In the first patient, serum was collected after plasmapheresis and in the second patient before plasmapheresis.…”
Section: Diagnosissupporting
confidence: 69%
See 2 more Smart Citations
“…This observation was further supported by Jansen et al. () , who reported two cases of BDUMP in whom serum were collected. In the first patient, serum was collected after plasmapheresis and in the second patient before plasmapheresis.…”
Section: Diagnosissupporting
confidence: 69%
“…; Jansen et al. ; Schelvergem et al. ) and in two of four cases treated with plasma exchange (Jaben et al.…”
Section: Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…OCT shows subretinal fluid, hyperreflective spots, and an irregular thickened RPE. At the level of the RPE, en face OCT shows dark spots which correspond to hyperfluorescence spots on the blue-light autofluorescence (Jansen et al, 2015). The visual symptoms can precede discovery of the primary tumor.…”
Section: Rippsmentioning
confidence: 99%
“…Miles et al (2012) suggested the presence of an antibody that induced melanocyte proliferation. This syndrome, now also called bilateral diffuse uveal melanocytic proliferation, responds to plasma exchange (Miles et al, 2012;Jansen et al, 2015), but the cause is unknown.…”
Section: Rippsmentioning
confidence: 99%